Transmission Genetics of a Sorghum bicolor × S. halepense Backcross Populations - Kong, Wenqian; Nabukalu, Pheonah; Cox, T. Stan; Goff, Valorie H.; Pierce, Gary J.; Lemke, Cornelia; Robertson, Jon S.; Compton, Rosana; Tang, Haibao; Paterson, Andrew H. (Frontiers in Plant Science, 2020)
Despite a “ploidy barrier,” interspecific crosses to wild and/or cultivated sorghum (Sorghum bicolor, 2n = 2x = 20) may have aided the spread across six continents of Sorghum halepense, also exemplifying risks of “transgene escape” from crops that could make weeds more difficult to control. Genetic maps of two BC1F1 populations derived from crosses of S. bicolor (sorghum) and S. halepense with totals of 722 and 795 single nucleotide polymorphism (SNP) markers span 37 and 35 linkage groups, with 2–6 for each of the 10 basic sorghum chromosomes due to fragments covering different chromosomal portions or independent segregation from different S. halepense homologs. Segregation distortion favored S. halepense alleles on chromosomes 2 (1.06–4.68 Mb, near a fertility restoration gene), 7 (1.20–6.16 Mb), 8 (1.81–5.33 Mb, associated with gene conversion), and 9 (47.5–50.1 Mb); and S. bicolor alleles on chromosome 6 (0–40 Mb), which contains both a large heterochromatin block and the Ma1 gene. Regions of the S. halepense genome that are recalcitrant to gene flow from sorghum might be exploited as part a multi-component system to reduce the likelihood of spread of transgenes or other modified genes. Its SNP profile suggests that chromosome segments from its respective progenitors S. bicolor and Sorghum propinquum have extensively recombined in S. halepense. This study reveals genomic regions that might discourage crop-to-weed gene escape, and provides a foundation for marker-trait association analysis to determine the genetic control of traits contributing to weediness, invasiveness, and perenniality of S. halepense.